2021
DOI: 10.3390/app11188436
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Degradation Mechanism from Shear Deformation and the Relationship with Mechanical Properties, Lamellar Size, and Morphology of High-Density Polyethylene

Abstract: The degradation of mechanical properties is the most challenging point for the development of plastic mechanical recycling processes. Remelting and shear deformation contained in the mechanical process are a part of degradation in recycled plastics. In this study, virgin high-density polyethylene (HDPE) was simulated to be recycled by remelting and treating with shear deformation being measured at different shear treatment rates (0–100/s) using a cone-plate rheometer. The obtained shear treatment product was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Kaneyasu et al [25] investigated the mechanism of steady shear deformation of HDPE. Mechanical recycling process was performed by steady shear treatment by using a cone and plate rheometer.…”
Section: Physical Degradation Of Plastics From Shear Deformation: The...mentioning
confidence: 99%
See 2 more Smart Citations
“…Kaneyasu et al [25] investigated the mechanism of steady shear deformation of HDPE. Mechanical recycling process was performed by steady shear treatment by using a cone and plate rheometer.…”
Section: Physical Degradation Of Plastics From Shear Deformation: The...mentioning
confidence: 99%
“…From this study, it can be evidence that steady shear treatment which was generally detected in the mechanical recycling process affected the degradation of mechanical properties which can be also related to the changes of thickness of lamellar structure and mesoscale surface morphology of HDPE (Figure 9). [25].…”
Section: Physical Degradation Of Plastics From Shear Deformation: The...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is evidenced from oscillatory shear deformation studies that lamellar crystal growth can be controlled in plastics by tuning the process conditions, which enhances the mechanical strength of the materials by a thousand-fold [17][18][19]. Additionally, the static shear deformation proved that lamellar crystal axis (C-axis) growth occurs perpendicular to the direction of deformation [20][21][22]. Using such approaches, it could be concluded that processing techniques are crucial in shaping industrial products.…”
Section: Introductionmentioning
confidence: 99%